An innovative phase 2 proof-of-concept trial design to evaluate SAR445088, a monoclonal antibody targeting complement C1s in chronic inflammatory demyelinating polyneuropathy - Querol, Luis; Lewis, Richard A; Hartung, Hans-Peter; Van Doorn, Pieter A; Wallstroem, Erik; Luo, Xiaodong; Alonso-Alonso, Miguel; Atassi, Nazem; Hughes, Richard A C (Journal of the peripheral nervous system, 2023)
BACKGROUND AND AIMS: Chronic inflammatory demyelinating polyneuropathy (CIDP) is a rare immune-mediated disease of the peripheral nerves, with significant unmet treatment needs. Clinical trials in CIDP are challenging; thus, new trial designs are needed. We present design of an open-label phase 2 study (NCT04658472) evaluating efficacy and safety of SAR445088, a monoclonal antibody targeting complement C1s, in CIDP. METHODS: This phase 2, proof-of-concept, multicenter, open-label trial will evaluate the efficacy, and safety of SAR445088 in 90 patients with CIDP across three groups: (1) currently treated with standard-of-care (SOC) therapies, including immunoglobulin or corticosteroids (SOC-Treated); (2) refractory to SOC (SOC-Refractory); and (3) naïve to SOC (SOC-Naïve). Enrolled participants undergo a 24-week treatment period (part A), followed by an optional treatment extension for up to an additional 52 weeks (part B). In part A, the primary endpoint for the SOC-Treated group is the percentage of participants with a relapse after switching from SOC to SAR445088. The primary endpoint for the SOC-Refractory and SOC-Naïve groups is the percentage of participants with a response, compared to baseline. Secondary endpoints include safety, tolerability, immunogenicity, and efficacy of SAR445088 during 12-week overlapping period (SOC-Treated). Part B evaluates long-term safety and durability of efficacy. Data analysis will be performed using Bayesian statistics (predefined efficacy thresholds) and historical data-based placebo assumptions to support program decision-making. INTERPRETATION: This innovative trial design based on patient groups and Bayesian statistics provides an efficient paradigm to evaluate new treatment candidates across the CIDP spectrum and can help accelerate development of new therapies.
Keywords: komplement C1s; Bayes Theorem; Antibodies, Monoclonal; výsledek terapie; Proof of Concept Study; lidé; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; Bayesova věta; hormony kůry nadledvin; Adrenal Cortex Hormones; Complement C1s; Treatment Outcome; monoklonální protilátky; Humans; ověření koncepční studie; chronická zánětlivá demyelinizační polyneuropatie